Fair and anonymous ID-based multi-receiver signcryption - Liao-jun PANG; Lu GAO; Qing-qi PEI; Yu-min WANG (Tongxin xuebao)
In order to solve the identify information exposure problem and the decryption unfairness problem in Lal et al’s identity-based multi-receiver signcryption scheme,a novel identity-based multi-receiver signcryption scheme,using the Lagrange interpolation method,was proposed to meet the requirements of the identity anonymity and the decryption fairness.Based on the Bilinear Diffie-Hellman and computational Diffie-Hellman assumptions,the security of IND-sMIBSC-CCA2 and EUF-sMIBSC-CMA was proved formally under the random oracle model,which shows that the proposed scheme can achieve the confidentiality and the unforgeablity required.